2016
DOI: 10.1098/rspb.2015.2397
|View full text |Cite
|
Sign up to set email alerts
|

Dietary exposure to an environmental toxin triggers neurofibrillary tangles and amyloid deposits in the brain

Abstract: Neurofibrillary tangles (NFT) and β-amyloid plaques are the neurological hallmarks of both Alzheimer's disease and an unusual paralytic illness suffered by Chamorro villagers on the Pacific island of Guam. Many Chamorros with the disease suffer dementia, and in some villages one-quarter of the adults perished from the disease. Like Alzheimer's, the causal factors of Guamanian amyotrophic lateral sclerosis/parkinsonism dementia complex (ALS/PDC) are poorly understood. In replicated experiments, we found that ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
144
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(146 citation statements)
references
References 50 publications
2
144
0
Order By: Relevance
“…One of the most debated hypotheses has been the dietary intake of a cyanobacterial toxin present in the traditional Chamorro diet, β-N-methylamino-l-alanine. There are basic laboratory and animal evidences that this compound promotes both NFT and β-amyloid deposits [45,46], similar to the deposit found in the brain of Chamorros affected individuals.…”
Section: Als Foci In the Worldmentioning
confidence: 99%
“…One of the most debated hypotheses has been the dietary intake of a cyanobacterial toxin present in the traditional Chamorro diet, β-N-methylamino-l-alanine. There are basic laboratory and animal evidences that this compound promotes both NFT and β-amyloid deposits [45,46], similar to the deposit found in the brain of Chamorros affected individuals.…”
Section: Als Foci In the Worldmentioning
confidence: 99%
“…BMAA is a neurotoxic amino acid which can be incorrectly insert into the polypeptide chains of brain proteins and then lead to protein misfolding, a hallmark characteristic of A plaque in AD patients (Mulligan and Chakrabartty, 2013). Recent research found that chronic dietary exposure to cyanobacterial toxin BMAA triggered NFT and A deposits in the brain and increased the risk of AD (Cox et al, 2016). Other cyanobacteria produced neurotoxins including saxitoxin and anatoxin- may further lead to neurological diseases, especially in the process of aging (Brenner, 2013).…”
Section: The Influence Of Gut Microbiota On Neurochemical and Metabolmentioning
confidence: 99%
“…The importance of biofilms and biofilm-dispersing agents in the prevention of Alzheimer's disease, particularly L-serine, is eloquently illustrated in the observations of Cox et al As an ethnobiologist, Dr. Cox was particularly fascinated with the markedly increased incidence of Lou Gehrig's, Parkinson's, and Alzheimer's diseases among the Chamorro people of Guam [84]. This was attributed to a unique diet high in beta-Methylamino-L-alanine (BMAA), a neurotoxic substance [84].…”
Section: Topical Systemicmentioning
confidence: 99%
“…This was attributed to a unique diet high in beta-Methylamino-L-alanine (BMAA), a neurotoxic substance [84]. Meanwhile, distant Ogimi villagers on the Japanese island of Okinawa who ate a diet of tofu and seaweed that contained large quantities of L-serine did not have these diseases, nor did they have high rates of arthritis [82].…”
Section: General Paresis Of the Insane And Alzheimer's Diseasementioning
confidence: 99%